A dual-salt coupled fluoroethylene carbonate succinonitrile-based electrolyte enables Li-metal batteries. Issue 4 (8th January 2020) - Fu, Chuankai; Ma, Yulin; Lou, Shuaifeng; Cui, Can; Xiang, Lizhi; Zhao, Wei; Zuo, Pengjian; Wang, Jiajun; Gao, Yunzhi; Yin, Geping
Abstract : We report a novel succinonitrile (SN)-based electrolyte SN–DLi–FEC (SN–LiTFSI–LiODFB–FEC), which shows excellent compatibility with the Li-metal anode. Abstract : Succinonitrile (SN)-based electrolytes are attractive due to their considerable ionic conductivity and high oxidative stability. However, the spontaneous chemical side-reactions between SN and Li-metal restrict the extensive applications of such electrolytes in next-generation advanced Li-metal batteries. Herein, we report a novel SN-based electrolyte SN–DLi–FEC which combines the dual-salt (lithium bis(trifluoromethane sulfonimide) (LiTFSI) and lithium difluoro(oxalato)borate (LiODFB)) and the fluoroethylene carbonate (FEC) additive. Compared with other SN-based electrolytes such as SN–SLi–FEC (single salt combined with FEC), SN–DLi–FEC can form a more stable and durable organic–inorganic composite SEI film rich in the B–F bond and LiF on the surface of the Li-metal anode. As a result, interfacial compatibility of the SN-based electrolytes and the Li-metal anode can be significantly enhanced. Moreover, SN–DLi–FEC shows high oxidation resistance, high ionic conductivity and good thermal stability. The LiCoO2 (LCO)/Li battery equipped with SN–DLi–FEC exhibits excellent electrochemical performances at room temperature (RT) and high temperature, and high thermal safety. The novel SN-based electrolyte prepared in this work could be a promising candidate providing better reliability and safety for the development of Li-metal batteries.